1981
DOI: 10.1007/bf01721923
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of oxazepam in relation to age, sex, and cigarette smoking

Abstract: The kinetics of single 30-mg oral doses of oxazepam were determined in 22 male and nine female volunteers aged 20-86 years. Oxazepam plasma concentrations were measured in multiple plasma samples drawn during 36 h after each dose. Mean kinetic variables in males and females, respectively, were: elimination half-life, 7.5 and 8.5 h; volume of distribution, 0.96 and 1.17 l/kg; clearance, 1.48 and 1.70 ml/min/kg. Sex differences were not significant, nor were any of the kinetic variables significantly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
3
22
1
Order By: Relevance
“…Bock et al [1987] found an increased urinary ex cretion ratio of intact acetaminophen di vided by acetaminophen metabolites, but the plasma clearance of acetaminophen was not evaluated. The benzodiazepine deriva tives, oxazepam and lorazepam, are biotransformed mainly by glucuronide conjuga tion , Ochs et al [1981] found significantly enhanced clearance of oxazepam among cigarette smokers, but this was not true for lorazepam [Ochs et al, 1985],…”
Section: Discussionmentioning
confidence: 95%
“…Bock et al [1987] found an increased urinary ex cretion ratio of intact acetaminophen di vided by acetaminophen metabolites, but the plasma clearance of acetaminophen was not evaluated. The benzodiazepine deriva tives, oxazepam and lorazepam, are biotransformed mainly by glucuronide conjuga tion , Ochs et al [1981] found significantly enhanced clearance of oxazepam among cigarette smokers, but this was not true for lorazepam [Ochs et al, 1985],…”
Section: Discussionmentioning
confidence: 95%
“…Dragacci et al showed no effect of smoking on bilirubin (UGT1A1) or clofibrate (UGT2B7) glucuronidation in microsomes from liver biopsies (Dragacci et al, 1987). Results from several in vivo studies suggest that the clearance of acetaminophen (Bock et al, 1994; Bock et al, 1987), oxazepam (Ochs et al, 1981), and codeine (Yue et al, 1989; Yue et al, 1994) is higher in cigarette smokers, although the extent of the difference was small and probably clinically unimportant. In contrast, results of several other studies show no effects of smoking on the clearance by glucuronidation of acetaminophen (Miners et al, 1984; Scavone et al, 1990), diflunisal (Macdonald et al, 1990), and lorazepam (Ochs et al, 1985).…”
Section: Interindividual Variability In Activity Of the Major Ugt Isomentioning
confidence: 99%
“…Published articles have studied pharmacokinetics of this drug [2][3][4]. There are also reports of tobacco smoke affecting pharmacokinetics of various drugs; Elimination rate was increased in theophylline [5][6][7], imipramine [8], propranolol [9] and oxazpam [10] in smoker subjects. No difference was observed in multiple dose pharmacokinetics of phenobarbital in nonsmokers in comparison with the smokers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%